Study of a supplement and a genetic test for lymphedema management - Michelini, Sandro; Cestari, Marina; Michelini, Serena; Camilleri, Giorgio; De Antoni, Luca; Sonna, Willy Nelson; Bertelli, Matteo (Acta Biomedica Atenei Parmensis, 2020)
Malformations in the lymphatic vasculature, injury, surgery, trauma or toxic damage may lead to swelling of the limbs caused by inefficient lymphatic uptake and flow (lymphedema). Lymphedema can be congenital or acquired. Primary lymphedema is rare and caused by mutations in single genes, secondary lymphedema is more common and caused by a trauma in association with a genetic predisposition. We decided to develop a genetic test that would determine the genetic predisposition to the onset of lymphedema and to predict the course of the disease by analyzing polymorphisms involved in leukotriene B4 (LTB4) synthetic pathway, and variants involved in the onset of secondary lymphedema. There are not many compounds available for the treatment of the negative effects of lymph accumulation, we therefore designed a food supplement based on the hydroxytyrosol, that has anti-oxidant, anti-bacterial and anti-inflammatory activities.